The Inhibitory Effects of New Zealand Pine Bark (Enzogenol®) on α-Amylase, α-Glucosidase, and Dipeptidyl Peptidase-4 (DPP-4) Enzymes. - Lim WXJ; Gammon CS; von Hurst P; Chepulis L; Page RA (MDPI (Basel, Switzerland))
The New Zealand pine bark extract (Enzogenol®) has previously been shown to elicit acute hypoglycaemic effects in humans. The present study investigated the underlying mechanisms of Enzogenol® in reducing postprandial glucose in humans. The potential inhibitory action of Enzogenol® against digestive enzymes: α-amylase and α-glucosidase, and dipeptidyl peptidase-4 (DPP-4) enzyme was determined. Enzogenol® demonstrated the ability to inhibit all three enzymes: α-amylase enzyme activity (IC50 3.98 ± 0.11 mg/mL), α-glucosidase enzyme activity (IC50 13.02 ± 0.28 μg/mL), and DPP-4 enzyme activity (IC50 2.51 ± 0.04 mg/mL). The present findings indicate the potential for Enzogenol® to improve postprandial glycaemia by delaying carbohydrate digestion via the inhibition of digestive enzymes (α-amylase and α-glucosidase), and enhancing the incretin effect via inhibiting the dipeptidyl-peptidase-4 enzyme. The inhibitory actions of Enzogenol® on enzymes should therefore be further validated in humans for its potential use in type 2 diabetes mellitus prevention and management.
Keywords: functional food; hyperglycaemia; hypoglycaemic effects; impaired glycaemic control; incretin effect; polyphenol; starch inhibition; Diabetes Mellitus, Type 2; Dipeptidyl-Peptidase IV Inhibitors; Flavonoids; Glycoside Hydrolase Inhibitors; Humans; New Zealand; Pinus; Plant Bark; Plant Extracts; Quercetin; alpha-Amylases; alpha-Glucosidases; 0908 Food Sciences; 1111 Nutrition and Dietetics